The Gut Microbiome and Xenobiotics: Identifying Knowledge Gaps. (25th June 2020) - Sutherland, Vicki L; McQueen, Charlene A; Mendrick, Donna; Gulezian, Donna; Cerniglia, Carl; Foley, Steven; Forry, Sam; Khare, Sangeeta; Liang, Xue; Manautou, Jose E; Tweedie, Donald; Young, Howard; et al.
Abstract: There is an increasing awareness that the gut microbiome plays a critical role in human health and disease, but mechanistic insights are often lacking. In June 2018, the Health and Environmental Sciences Institute (HESI) held a workshop, "The Gut Microbiome: Markers of Human Health, Drug Efficacy and Xenobiotic Toxicity" (https://hesiglobal.org/event/the-gut-microbiome-workshop ) to identify data gaps in determining how gut microbiome alterations may affect human health. Speakers and stakeholders from academia, government, and industry addressed multiple topics including the current science on the gut microbiome, endogenous and exogenous metabolites, biomarkers, and model systems. The workshop presentations and breakout group discussions formed the basis for identifying data gaps and research needs. Two critical issues that emerged were defining the microbial composition and function related to health and developing standards for models, methods and analysis in order to increase the ability to compare and replicate studies. A series of key recommendations were formulated to focus efforts to further understand host-microbiome interactions and the consequences of exposure to xenobiotics as well as identifying biomarkers of microbiome-associated disease and toxicity.